Histologic Subtype Defines the Risk and Kinetics of Recurrence and Death for Primary Extremity/Truncal Liposarcoma. Issue 6 (June 2021) - Bartlett, Edmund K.; Curtin, Christina E.; Seier, Kenneth; Qin, Li-Xuan; Hameed, Meera; Yoon, Sam S.; Crago, Aimee M.; Brennan, Murray F.; Singer, Samuel
Abstract : Objective: We sought to define the prognostic significance of histologic subtype for extremity/truncal liposarcoma (LPS). Background: LPS, the most common sarcoma, is comprised of 5 histologic subtypes. Despite their distinct behaviors, LPS outcomes are frequently reported as a single entity. Methods: We analyzed data on all patients from a single-institution prospective database treated from July 1982 to September 2017 for primary, nonmetastatic, extremity or truncal LPS of known subtype. Clinicopathologic variables were tested using competing risk analyses for association with disease-specific death (DSD), distant recurrence (DR), and local recurrence (LR). Results: Among 1001 patients, median follow-up in survivors was 5.4 years. Tumor size and subtype were independently associated with DSD and DR. Size, subtype, and R1 resection were independently associated with LR. DR was most frequent among pleomorphic and round cell LPS; the former recurred early (43% by 3 years), and the latter over a longer period (23%, 3 years; 37%, 10 years). LR was most common in dedifferentiated LPS, in which it occurred early (24%, 3 years; 33%, 5 years), followed by pleomorphic LPS (18%, 3 years; 25%, 10 years). Conclusions: Histologic subtype is the factor most strongly associated with DSD, DR, and LR in extremity/truncal LPS. Both risk and timing of adverse outcomes vary by subtype. These data may guide selective use of systemic therapy for patients with round cell and pleomorphic LPS, which carry a high risk of DR, and radiotherapy for LPS subtypes at high risk of LR when treated with surgery alone. Abstract : Supplemental Digital Content is available in the text